2017
DOI: 10.18632/oncotarget.17849
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cumulative prognostic score based on pretreatment plasma fibrinogen and serum albumin levels in patients with newly diagnosed high-grade gliomas

Abstract: This retrospective study was designed to determine the prognostic value of a cumulative score (FA score) based on pretreatment plasma fibrinogen and serum albumin levels for 326 patients newly diagnosed high-grade glioma (HGG). Receiver operating characteristic (ROC) curve analysis was performed to determine the optimal cut-off values. Univariate and multivariate analysis were performed to evaluate the independent prognostic value of the FA scores associated with overall survival (OS) and progression-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Fibrinogen was shown to play important roles both in tumor cell proliferation, migration and angiogenesis and as regulator of inflammation in solid tumors. They conclude that higher pretreatment FA score was an independent prognostic factor of PFS and OS of patients with high-grade gliomas and was significantly associated with advanced age and higher tumor grade [86].…”
Section: Biomarkers Related To Nutritional Statusmentioning
confidence: 96%
“…Fibrinogen was shown to play important roles both in tumor cell proliferation, migration and angiogenesis and as regulator of inflammation in solid tumors. They conclude that higher pretreatment FA score was an independent prognostic factor of PFS and OS of patients with high-grade gliomas and was significantly associated with advanced age and higher tumor grade [86].…”
Section: Biomarkers Related To Nutritional Statusmentioning
confidence: 96%
“…There were numerous studies suggested that high plasma fibrinogen levels were associated with worse clinical outcome in a variety of solid tumors 6 . The prognostic value of plasma fibrinogen was also proven in human gliomas 7 , 8 . Nevertheless, the reliability and degree of this prognostic marker needed to be re-evaluated, due to limited cases and variation in study designs.…”
Section: Introductionmentioning
confidence: 95%
“…The Glasgow Prognostic Score (GPS), which combines serum CRP with albuminemia and has been demonstrated to be a predictive factor in various cancers, is regarded as a prognostic milestone among all the systems (Forrest, McMillan, & McArdle, ; McMillan, ). Other prognostic systems such as neutrophil to lymphocyte ratio (NLR) (Cho et al, ; McNamara et al, ; Tajiri et al, ), platelet to lymphocyte ratio (PLR) (Kwon, Kim, & Oh, ; Li et al, ), and fibrinogen (He et al, ; Luo, Kim, Kim, Lee, & Song, ; Seebacher et al, ), can help predict the progression, metastasis, and prognosis of cancer patients.…”
Section: Introductionmentioning
confidence: 99%